Virgen de la Misericordia, San Jerónimo y San Miguel: el origen del corporativismo sedero en la Valencia bajomedieval (1465-1518). - MARTÍNEZ VINAT, JUAN (Scripta, 2017)
This essay enquires into the origins of the Valencian silk coorporativism though the three main guilds of late medieval Valencia: the confraternity of The Mercy of silk weavers, the confraternity of Saint Jerome of the Art de Velluters, and the confraternity of Saint Michaels' silk dyers. The analysis of their rules will be contrasted with account records (Llibres de Dates e Rebudes). This will allow finding out the functioning and development of these three entities, which proved essential for the trigger of Valencian silk industry. Such an analysis will be conducted both from a work and relief-based view since these ar inseparable in this period.